Cardiac parasympathetic reactivation following small-sided games, repeated sprints and circuit training in elite handball players - Ravier, G.; Marcel-Millet, P. (Journal of Human Kinetics, 2020)
To compare acute parasympathetic reactivation following usual training exercises, the acute post-exercise heart rate (HR) and heart rate variability (HRV) were analysed. Fourteen elite male handball players completed three separate sessions of 16-min small-sided games (SSGs), repeated sprints (RSs) consisting of two sets of six repetitions of a 25-m sprint with a 180° change of direction (12.5 m + 12.5 m) every 25 s and 40 min of handball-specific circuit training (CT, one brief action every 40 s). The HR was recorded during the exercises; HRV was assessed 10 min before and after exercise. The exercise HR was higher for SSGs than RSs and it was higher for RSs than CT. Comparison of the baseline and acute post-exercise HRV values showed that parasympathetic indices decreased following SSG (p < 0.01 - p < 0.0001; large effect size) and RS (p < 0.05 -p < 0.01; large effect size) interventions. For CT, recovery values remained similar to the baseline (small effect size). The comparison of the acute recovery period between exercise modalities showed that the root mean square of the successive differences (RMSSD) was lower for SSGs than RSs and CT. No difference in any HRV indices was observed between RSs and CT. Time-varying of RMSSD for successive 30 s segments during the 10 min recovery period showed lower values for SSGs than CT for all tested points; the progressive increase in the beat-to-beat interval was similar for all interventions. In conclusion, SSGs caused the greatest post-exercise vagal disruption and it is likely that CT is the exercise modality that least delays over-all recovery. These results might help coaches design better training sessions by understanding athletes` recovery status after completing their conditioning exercises.